Aesthetic consideration in patient management of severe periodontitis aggravated by oral dexamethasone - Irma Josefina Savitri; I Komang Evan Wijaksana; Okkinardo Arief; Muhammad Nur Falah; Udijanto Tedjosasongko; Olivia Bambang Siswanto; Kazuhisa Ouhara; Hidemi Kurihara; Noriyoshi Mizuno (Dental Journal, 2023)
Background: The treatment of severe periodontitis must consider immune responses and local conditions, including the aesthetical aspects. The tooth loss in the anterior area can lead to a psychological issue in some patients, and the daily use of dexamethasone contributes greatly to the severity of aesthetical aspects. Periodontal treatments must be cautious of these aesthetical effects. Purpose: To report the aesthetical consideration in patient management of severe periodontitis aggravated by oral dexamethasone. Case: The 44-year-old female patient reported having tooth mobility in the upper right and left central incisor and lower right and left posterior. Due to the condition, the central anterior needed to be extracted. The patient had seafood allergies and consumed oral dexamethasone periodically to prevent allergic reactions for two years. Case management: The initial periodontal therapy was designed prior to the tooth extraction, socket preservation, and immediate denture on teeth 11 and 21. A metal frame combined with an acrylic denture was designed to support the tooth splint and replace the teeth on the mandible. The patient was treated with 20 mg of sub-antimicrobial-dose doxycycline twice a day for three months, and vitamin E was prescribed once a day. Since dexamethasone may contribute to immune response and osteoclastogenesis, dexamethasone was replaced by cetirizine. Conclusion: The treatment of severe chronic periodontitis must consider immune responses, local conditions, and aesthetical aspects. In this case, the use of dexamethasone might worsen the periodontal breakdown. However, the periodontal treatment, use of host modulation therapy, and replacement of dexamethasone with cetirizine are expected to improve these conditions.